The Meagerness of Simple Likert Scale in Assessing Risk: How Appropriate the Fuzzy Likert is? - A.K.M. Kanak Pervez; Md. Maniruzzaman; Ashfaq Ahmad Shah; Nur Nabi; Abdou Matsalabi Ado (NUST Journal of Social Sciences and Humanities, 2021)
Social scientists around the world commonly use the Likert scale. The scale has some limitations; in many cases, researchers are ignoring those limitations. Many social scientists have been trying to find out an alternative, but all initiatives do not correctly solve the problems. Among all limitations, the most critical issue is that Likert scale adopts a similar variance between two successive scale points. Fuzzy-Likert scale is a useful alternative for solving the existing limitation of the traditional Likert scale. Therefore, the current article describes the limitations of existing Likert scale and application of Fuzzy-Likert scale in perceived risk assessment. Naturally, risks are interrelated with different factors. Assessing risks with simple existing Likert scale is not entirely appropriate. A well-structured Fuzzy-Likert scale can be used to mitigate the existing problems. This article clarifies how efficiently researchers can use a Fuzzy-Likert scale for assessing the perceived risk in agriculture using a simple structured questionnaire with the help of an example. To reach the conclusions and recommendations, the researchers used different published articles, online repositories, report etc. through content analysis.